Crop and residue management improves productivity and profitability of rice-maize system in salt-affected rainfed lowlands of East India - Sarangi, Sukanta K.; Singh, Sudhanshu; Srivastava, Ashish K.; Choudhary, Madhu; Mandal, Uttam K.; Lama, Tashi D.; Mahanta, Kshirendra K.; Kumar, Virender; Sharma, Parbodh C.; Ismail, Abdelbagi M. (MDPI, 2020)
This study was conducted over 3 years in a salt-affected coastal rainfed lowland ecosystem. Farmers most commonly grow tall rice varieties in the wet season to cope with flash and/or stagnant floods, leading to large amounts of rice residue production. Most of the land remains fallow during the dry season because of increased salinity and scarcity of freshwater for irrigation. The study aims to provide options for increasing cropping intensity through management of crop residues (CR) and soil salinity, conservation of soil moisture, and reduction in production cost. The rice–maize rotation was assessed with rice as the main plot as (1) puddled transplanted rice (PTR) with CR of both rice and maize removed, (2) PTR and 40% CR of both crops retained, (3) dry direct-seeded rice (DSR) with CR of both crops removed, and (4) DSR with 40% CR of both crops retained. Maize in the dry season was supplied with different N levels as sub-plots—control (0 kg N ha−1), 80, 120, and 160 kg N ha−1. DSR, when combined with CR retention (DSR + R), reduced soil salinity. The increase in rice grain yield with CR retention (observed in second and third years) and crop establishment (higher in DSR versus PTR in the third year) was 16 and 24%, respectively. The cost of production increased by 17% (USD 605 ha−1) in PTR compared with DSR (USD 518 ha−1). CR retention reduced irrigation water requirement by 37% and N requirement by 40 kg ha−1 for hybrid maize. When CR was removed (−R), the N requirement for hybrid maize increased to 160 kg N ha−1 compared to when it was partially (40%) retained, where the requirement was 120 kg ha−1 with similar yields. Available N was highest under DSR + R (314 kg ha−1) and lowest under PTR − R (169 kg ha−1), and it also increased with increasing N application up to 120 kg ha−1 (+R) and 160 kg ha−1 (−R). The results of the study hold promise for increasing cropping intensity and farmers’ incomes, with broader implications for increasing productivity on about 2.95 million hectares currently under a rice–fallow system in eastern India, and in coastal areas affected by similar conditions in South and Southeast Asia.